Studi Kasus pada Bidang Penempatan dan Perluasan Kerja terhadap Tingkat Pendidikan Tahun 2010 – 2020 di Dinas Ketenagakerjaan Kota Balikpapan Menggunakan Metode Analisis Profil - Anitaria Tandean; Syalam Ali Wira Dinata (LPPM ITK, 2022)
Balikpapan City Manpower Office as 3 (three) fields, and one of them is the Field of Placement and Job Expansion. The Job Placement and Expansion Sector has annual profile data which is recorded at the Disnaker Balikpapan. The profile data used for this research is job seeker data, job vacancies, job placement (received) to the level of education. The method used for this research is Profile Analysis, which is a statistical method for analyzing data with more than two dependent variables together. This profile analysis aims to determine the characteristics of two independent populations. One of the characteristics of the population is to test the hypothesis, the hypothesis test used is the parallel test, coincident test, and similarity (level test). for each population. So that the Profile Analysis method is used to determine the characteristics of the population in the Job Placement and Expansion Sector at the Balikpapan City Manpower Office.